Jacopo Strada and Cultural Patronage at The Imperial Court (2 Vols.) The Antique as Innovation - Jansen, Dirk (Rulers & Elites, 2019)
In Jacopo Strada and Cultural Patronage at the Imperial Court: Antiquity as Innovation, Dirk Jansen provides a survey of the life and career of the antiquary, architect, and courtier Jacopo Strada (Mantua 1515-Vienna 1588). His manifold activities - also as a publisher and as an agent and artistic and scholarly advisor of powerful patrons such as Hans Jakob Fugger, the Duke of Bavaria and the Emperors Ferdinand I and Maximilian II - are examined in detail, and studied within the context of the cosmopolitan learned and courtly environments in which he moved. These volumes offer a substantial reassessment of Strada's importance as an agent of change, transmitting the ideas and artistic language of the Italian Renaissance to the North.